2004
DOI: 10.1038/sj.npp.1300411
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action Underlying the Effect of Repetitive Transcranial Magnetic Stimulation on Mood: Behavioral and Brain Imaging Studies

Abstract: In a set of experiments, we applied 10-Hz repetitive transcranial magnetic stimulation (rTMS) over the left mid-dorsolateral frontal cortex (MDLFC) to investigate rTMS-induced changes in affective state and neural activity in healthy volunteers. In Experiment 1, we combined 10-Hz rTMS with a speech task to examine rTMS-induced changes in paralinguistic aspects of speech production, an affect-relevant behavior strongly linked to the ACC. In Experiment 2, we combined 10-Hz rTMS with positron emission tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 76 publications
1
46
0
Order By: Relevance
“…Previous research by Barrett et al (2004) has demonstrated that stimulation near the areas we targeted in this study can result in changes in mood and affect, although stimulation parameters in the study by Barrett and colleagues (i.e. cathode location, specific anode location, electrode size, and current strength) were somewhat different from those used in our research.…”
Section: Discussionmentioning
confidence: 67%
“…Previous research by Barrett et al (2004) has demonstrated that stimulation near the areas we targeted in this study can result in changes in mood and affect, although stimulation parameters in the study by Barrett and colleagues (i.e. cathode location, specific anode location, electrode size, and current strength) were somewhat different from those used in our research.…”
Section: Discussionmentioning
confidence: 67%
“…Current hypotheses on possible rTMS working mechanisms suggest that the neurobiological influence occurs at the subcortical level, such as the paraventricular nucleus (PVN) of the hypothalamus Keck, 2003). Prefrontal cortical stimulation not only results in enhanced neuronal activity under the stimulation coil locally, but spreads through transsynaptic transmission further to other prefrontal cortical areas, such as the anterior cingulate cortex (ACC), in subcortical structures implicated in the neurocircuitry of emotional processing (Paus et al, 2001;Nahas et al, 2001;Kimbrell et al, 2002;Barrett et al, 2004) and in the neurobiological mechanisms of controlling HPA-system responsiveness (Herman et al, 2005;Radley et al, 2006;Jankord and Herman, 2008). These cortico-subcortical innervations which project to the hypothalamus are branches of the basic loop that is connected to autonomic expression of emotion (Gray, 1999;Zahm, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has linked schizophrenia with a failure to integrate activity in distributed neural circuits [47][48][49][50]. rTMS has the potential to induce changes in remote, functionally connected brain areas [51,52] in addition to local effects. The application of sequential stimulation, aimed at the areas of the PFC and temporoparietal cortex, seems to be an interesting approach, with some evidence for reduction in not only negative but also positive schizophrenia symptoms and potentially improved working memory [53].…”
Section: Resultsmentioning
confidence: 99%